Initial Provider Specialty Is Associated With Long-term Opiate Use in Patients With Newly Diagnosed Low Back and Lower Extremity Pain. Issue 3 (1st February 2019) - Azad, Tej D.; Vail, Daniel; Bentley, Jason; Han, Summer S.; Suarez, Paola; Varshneya, Kunal; Mittal, Vaishali; Veeravagu, Anand; Desai, Manisha; Bhattacharya, Jay; Ratliff, John K.
Abstract : Study Design: Retrospective longitudinal cohort analysis of patients diagnosed in 2010, with continuous enrollment 6 months prior to and 12 months following the initial visit. Objective: To determine whether provider specialty influences patterns of opiate utilization long after initial diagnosis. Summary of Background Data: Patients with low back pain present to a variety of providers and receive a spectrum of treatments, including opiate medications. The impact of initial provider type on opiate use in this population is uncertain. Methods: We performed a retrospective analysis of opiate-naïve adult patients in the United States with newly diagnosed low back or lower extremity pain. We estimated the risk of early opiate prescription (⩽14 d from diagnosis) and long-term opiate use (≥six prescriptions in 12 mo) based on the provider type at initial diagnosis using multivariable logistic regression, adjusting for patient demographics and comorbidities. Results: We identified 478, 981 newly diagnosed opiate-naïve patients. Of these, 40.4% received an opiate prescription within 1 year and 4.0% met criteria for long-term use. The most common initial provider type was family practice, associated with a 24.4% risk of early opiate prescription (95% CI, 24.1–24.6) and a 2.0% risk of long-term opiate use (95% CI, 2.0–2.1). Risk of receiving an early opiate prescription was higher among patients initially diagnosed by emergency medicine (43.1%; 95% CI, 41.6–44.5) or at an urgent care facility (40.8%; 95% CI, 39.4–42.3). Risk of long-term opiate use was highest for patients initially diagnosed by pain management/anesthesia (6.7%; 95% CI, 6.0–7.3) or physical medicine and rehabilitation (3.4%; 95% CI, 3.1–3.8) providers. Conclusion: Initial provider type influences early opiate prescription and long-term opiate use among opiate-naïve patients with newly diagnosed low back and lower extremity pain. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textWe identified 478, 981 newly diagnosed, opiate-naïve low back pain patients. Risk of receiving an early opiate prescription was higher among patients initially diagnosed by emergency medicine or at an urgent care facility. Risk of long-term opiate use was highest for patients initially diagnosed by pain management/anesthesia or PM&R providers.